Analysis of the Impact of MSME Financing and Government Spending on Poverty Levels in South Sulawesi from 2017 to 2022 - Mahmud, Ikwan; Saiful, Saiful; Rais, Rasnindah Abu (Jurnal Pallangga Praja (JPP), 2024)
The poverty rate is still amongst the biggest problem to achieve national goals. the government through fiscal policy pays great attention to dealing with the problem. The objective of this study is to analyze the impact of fiscal policy through treasury variable proxies, or variables that are directly or indirectly related to the functions of dgt as a treasury institution in Indonesia. the variables are State Budget expenditures, KUR, and UMi. the study uses panel data, which is a combination of cross-sectional data in 24 regencies/ cities in South Sulawesi and time-series data from 2017 to 2022. the regression method used is the Random Effect Model (REM), also known as the Error Component Model (ECM). The results showed that all treasury variables are statistically significant to give a positive impact on reducing poverty rate in South Sulawesi.